Is it guns, people, or both? : A Critical Discourse Analysis of discursive strategies and topoi in United States’ gun control speeches of Donald Trump and Joe Biden in 2022 - Puhilas, Jani (My University, 2025)
This study examined the political messaging related to the gun control discourse of the United States during 2022. This particular year was chosen as focal point for the study due to a significant change in the gun legislation, which may have been influenced by two mass shootings that took place in in Buffalo, New York and Uvalde, Texas in 2022. The significant attention of U.S mass shootings also contributed to the choice of topic. Data for this study consisted two public speech videos, one from ex-president Donald Trump and the other from then-president Joe Biden who were chosen due to their significance in the United States politics. Critical Discourse Analysis (CDA) was adopted as the main theoretical approach for the analysis to assess each speech through a critical lens for power structures, stances, and ideologies. This framework was further complimented by discursive strategies and topoi adapted from the Discourse-historical approach (DHA) to examine the specific elements present in the messages each speaker conveyed in their respective speeches. The main findings made were that despite being generally very different in their discursive strategy and topoi use, both Trump and Biden did share similarities and that many of their statements did reflect their respective parties’ ideological views on gun control. Both also oversimplified the solutions to gun violence. For future studies, the examination of organisations and institutions related to the United States’ gun control is recommended to get a more comprehensive outlook on the discussion surrounding gun control.
Keywords: critical discourse analysis, discursive strategies, topoi, critical linguistics, united states, gun control